2021 IEEE International Joint Conference on Biometrics (IJCB) 2021
DOI: 10.1109/ijcb52358.2021.9484337
|View full text |Cite
|
Sign up to set email alerts
|

MFR 2021: Masked Face Recognition Competition

Abstract: This paper presents a summary of the Masked Face Recognition Competitions (MFR) held within the 2021 International Joint Conference on Biometrics (IJCB 2021). The competition attracted a total of 10 participating teams with valid submissions. The affiliations of these teams are diverse and associated with academia and industry in nine different countries. These teams successfully submitted 18 valid solutions. The competition is designed to motivate solutions aiming at enhancing the face recognition accuracy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…The number of trainable parameters in ResNet-34 and ResNet-18 is 21.3 million (m) and 11.8 m, respectively. Additionally, ResNet proposed the use of a small filter size of (32,16,8) In this work, we deployed ResNet-34 and ResNet-18 as teacher networks and the compact ResNet-110 as a student, as well as a stand-alone baseline. In order to adopt these models for periocular verification, we modified the number of classes in the classification layer to match the number of identities in our training dataset.…”
Section: Baseline Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of trainable parameters in ResNet-34 and ResNet-18 is 21.3 million (m) and 11.8 m, respectively. Additionally, ResNet proposed the use of a small filter size of (32,16,8) In this work, we deployed ResNet-34 and ResNet-18 as teacher networks and the compact ResNet-110 as a student, as well as a stand-alone baseline. In order to adopt these models for periocular verification, we modified the number of classes in the classification layer to match the number of identities in our training dataset.…”
Section: Baseline Modelsmentioning
confidence: 99%
“…These studies [9][10][11] concluded that the verification performance of face-recognition solutions significantly degraded when the subject was wearing a face mask, compared to the case where their face was unmasked. This was followed by several efforts to enhance masked face recognition [13][14][15], including competitions where some of the submitted solutions proposed the use of the periocular recognition [16,17]. Periocular biometrics have a distinct advantage over facial biometrics when the face is largely occluded or when capturing a full face is less convenient than capturing the periocular region (e.g., a selfie on a smartphone or masked face recognition [11], while maintaining the touchless nature of face capture.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some cases facial masks are used intentionally to trick the FR systems. Hence, many research activities focus on algorithms to increase FR performance when dealing with masks that cover a large area of an individual's face [29], [30].…”
Section: Related Workmentioning
confidence: 99%
“…Based on the position of these facial landmarks, a polygon is synthesized, simulating a digital face mask of different shapes, heights, and colors. The generation of the simulated masks is according to the method described in the NIST report [27] and the detailed implementation can be found on the repo 3 . For each face image, the mask type C as described in [2], [27] with random color is used to generate the synthetic masks in this work.…”
Section: A Databasementioning
confidence: 99%
“…Studies have been proposed to address the face occlusion problem, but most of them only address the occlusion in the wild, e.g., by wearing sunglasses. Only very recently, some works specifi-cally addressed the enhancement of masked face recognition performance [3], [2], [26].…”
Section: Introductionmentioning
confidence: 99%